Analisis Dampak Kebijakan Moneter terhadap Pertumbuhan Ekonomi di Indonesia - Rachmi Meutia; Muhammad Adnan; Lilis Kaslita (Jurnal Simki Economic, 2026)
Economic growth serves as a vital benchmark for national development and is the foundation of the sustainable development process. This study examines the effects of inflation, the money supply (M1), and the exchange rate on Indonesia's economic growth. Using a quantitative approach, this study analyzes secondary quarterly time series data from 2015–2023 sourced from Statistics Indonesia (BPS) and Bank Indonesia (BI). The Vector Error Correction Model (VECM) is applied to analyze the short- and long-term dynamics between these variables. The results show that in the long run, inflation does not significantly influence economic growth in Indonesia, while the money supply and the exchange rate have a significant influence on economic growth. Conversely, short-term estimation results indicate that the three independent variables of inflation, the money supply (JUB), and the exchange rate do not significantly influence fluctuations in national economic growth. As a policy implication, monetary authorities and the government need to maintain inflation stability and manage JUB liquidity and the exchange rate wisely to create a macroeconomic climate conducive to stable economic growth.